HUBUNGAN ANTARA LEADER MEMBER EXCHANGE DAN VOICE BEHAVIOR PADA KARYAWAN PT. SULUH ARDHI ENGINEERING - Azzahrah, Fatimah; Prihatsanti, Unika (Jurnal EMPATI, 2017)
This study aims to determine the relationship between leader member exchange and voice behavior on employees of PT. Suluh Ardhi Engineering. Voice behavior is an informal communication of an employee in the form of ideas, ideas, information, criticism or suggestions on problems that exist in the work environment and issues related to the organization. The research population are 100 employees who work as engineer at PT. Suluh Ardhi Engineering. The test was given to 50 engineer employees and the research was conducted to 50 engineer employees. The sampling technique used is simple random sampling. The measuring tool used in this research is the scale of voice behavior (28 item, α = .928) and leader exchange member scale (31 item, α = .960). Data analysis method used in this research with simple regression analysis. The results showed that there was a significant positive relationship between leader member exchange with voice behavior rxy = .71 with p = .000 (p <0.05). Leader member exchange contributes 49.2% effective to voice behavior.